Advancements and applications of loop-mediated isothermal amplification technology: a comprehensive overview - Yang, Nan; Zhang, Han; Han, Xiu; Liu, Zhifeng; Lu, Yan (Frontiers in Microbiology, 2024)
Loop-mediated isothermal amplification (LAMP) is a novel method for nucleic acid detection known for its isothermal properties, high efficiency, sensitivity, and specificity. LAMP employs 4 to 6 primers targeting 6 to 8 regions of the desired sequence, allowing for amplification at temperatures between 60-65℃ and the production of up to 10^9 copies within a single hour.The abundance of amplicons and by-products generated during LAMP amplification enables detection through The product can be monitored by various methods such as turbidimetry, fluorometry, and colorimetry, facilitating both real-time monitoring and endpoint analysis. However, it faces limitations such as the risk of non-specific amplification, challenges in primer design, unsuitability for short gene sequences, and difficulty in multiplexing.Recent advancements in polymerase and primer design have enhanced the speed and convenience of the LAMP reaction. Additionally, integrating LAMP with technologies like rolling circle amplification (RCA), recombinase polymerase amplification (RPA), and CRISPR-Cas systems has enhanced its efficiency. The combination of LAMP with various biosensors has enabled real-time analysis, broadening its application in point-of-care testing (POCT).Furthermore, the integration of LAMP with other technologies has broadened its potential applications.This paper provides an overview of the fundamental principles, monitoring methods, applications, and recent technical advancements in LAMP, as well as the synergistic applications of LAMP with other technologies . Microfluidic technology has further facilitated the automation and miniaturization of LAMP assays, allowing for the simultaneous detection of multiple targets and preventing contamination. This review highlights advancements in LAMP, focusing on primer design, polymerase engineering, and its integration with other technologies. Continuous improvements and integration of LAMP with complementary technologies have significantly enhanced its diagnostic capabilities, making it a robust tool for rapid, sensitive, and specific nucleic acid detection with promising implications for healthcare, agriculture, and environmental monitoring.